Innovative PLC network design for bit loading algorithm and bistatic channel capacity - Tae-Eung Sung (2009 IEEE 13th International Symposium on Consumer Electronics, 2009)
Block transmission is a very efficient scheme to combat with infer-symbol interference (ISI) caused by frequency-selective time-dispersive channels at the cost of interblock interference (IBI) occurring during block transmission. In particular, in order to suppress the IBI in the power-line communication (PLC) channel, we introduce a novel technique called lifting-trailing-zeros (LTZ). The power line channel is time-varying due to the appliances connected to outlets since appliances often exhibit input impedance that is a function of the instantaneous amplitude of the mains voltage which results in a periodically time-varying channel response. We here propose a discrete time-varying block channel model in the time domain, which allows for more realistic evaluation of modulation and coding strategies as well as for the design of bit loading strategies that can be resilient to the peculiar type of distortion in this harsh medium. Numerical results demonstrate the effectiveness of the proposed power line network simulator for bistatic channel capacity with water-filling which is compared with constant power bit-loading algorithm.